New exact solutions of the Dirac equation. V; Soviet Physics Journal; Vol. 18, iss. 9 - Bagrov V. G. Vladislav Gavriilovich; Byzov N. N.; Gitman D. M.; Klimenko Yu. I.; Meshkov A. G.; Shapovalov V. N.; Shakhmatov V. M. Valery Mikhailovich (1975, 1975)
Title screen